Fitness Fights Fires: Exploring the Relationship between Physical Fitness and Firefighter Ability - Annmarie Chizewski (MDPI AG, 2021)
Background: Regular exercise in firefighters may be effective in preventing or attenuating ill health (e.g., hypertension, diabetes, and obesity), as well as improving their firefighting ability. The purpose of this study was to investigate the relationship between physical fitness and firefighting ability. Methods: Male firefighter recruits’ (n = 89; age = 27.1 ± 4.2 yrs) physical fitness and firefighting ability were assessed at Week 1 and Week 7 during a basic firefighting training academy. Physical fitness was assessed via 1.5 mile run time, sit-up and push-up repetitions, the Young Men’s Christian Association (YMCA) bench press test, vertical jump height, and sit-and-reach flexibility, while firefighting ability was assessed via completion time on a firefighting skills test. Results: Fitness predicted significant variance in firefighting ability at Week 1 (R2= 0.46; p < 0.01) and Week 7 (R2 = 0.46; p < 0.01), after accounting for age and body mass index. Cardiovascular endurance accounted for 22.4% (FΔ (1, 85) = 25.75) and 39.3% (FΔ (1, 85) = 55.53) while muscular endurance accounted for an additional 19.0% (FΔ (3, 82) = 10.34) and 6.3% (FΔ (3, 82) = 3.2) unique variance in firefighting ability at Week 1 and Week 7, respectively. Conclusions: Given the strong association between fitness and firefighting performance, municipal departments may want to focus on increasing fitness levels among firefighters.